A Methodical Approach to a 15-Year Diagnostic Enigma: Unmasking Acrodermatitis Continua of Hallopeau Through Dermoscopy, Histopathology, and Structured Therapeutic Sequencing - Luh Putu Sustiana Kartika Sari; Ni Luh Putu Ratih Vibriyanti Karna (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Acrodermatitis continua of Hallopeau (ACH) is a rare, debilitating variant of pustular psoriasis. Its profound clinical mimicry of common infections, particularly onychomycosis, often leads to extensive diagnostic delays and ineffective treatments, causing significant patient morbidity. This report details a case with a 15-year history of misdiagnosis, illustrating a structured methodological approach to diagnosis and management. Case presentation: A 40-year-old Indonesian woman presented with a 15-year history of painful pustular lesions and severe onychodystrophy affecting seven digits, refractory to numerous antimicrobial therapies. The diagnostic process was systematically re-evaluated; dermoscopy revealed features inconsistent with onychomycosis (dotted vessels, hemorrhagic spots), prompting a definitive skin and nail matrix biopsy. Histopathology confirmed pustular psoriasis with pathognomonic Kogoj's spongiform pustules and Munro's microabscesses. Treatment was initiated with cyclosporine (3.3 mg/kg/day), leading to rapid remission. However, the development of gingival hyperplasia and hypertension necessitated a transition to weekly methotrexate (15 mg). The patient achieved and maintained clinical remission on this regimen. Conclusion: This case underscores the necessity of a high index of suspicion for ACH in chronic, treatment-resistant nail dystrophy. It demonstrates that a methodical application of dermoscopy and histopathology is indispensable for overcoming clinical mimicry. The main lesson is that structured diagnostic evaluation and sequenced therapy, responsive to adverse events, are crucial for achieving long-term remission and restoring quality of life.